PENGARUH FILM ANIMASI UPIN DAN IPIN TERHADAP PENERAPAN NILAI SOSIAL SISWA DI SDN 006 SEKOLUBUK TIGO LIRIK - Anwar, Rahmadianti; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The media has a huge influence on the direction of community life, as well as understanding of the mass media itself that the media are specifically designed to reach a very broad community. Type media itself is traditionally a newspaper, magazine, radio, and television. Audience needs will be met by the entertainment media as the existence of the shows presented by the mass media. In accordance with SOR theory, the theory of communication abbreviation of Stimulus-Organism-Response. According to this theory, the effect is specific reactions to specific stimuli, so that one can expect and predict compatibility between the message and the reaction communicant. The purpose of this research, ie determine whether there is influence elementary school students SDN 006 Sekolubuk Tigo Lirik in applying social values after watching the animated film Upin and Ipin.The method used in this research is quantitative method, the researchers collected data using questionnaires. The location of this research is the SDN 006 Sekolubuk Tigo Lirik. The number of samples for this study were 72 respondents, and the sampling itself using manual sampling techniques. To find out how much the relationship between the two variables, the researchers used linear regression analysis simplistic. As for the data processing of questionnaires, conducted using Statistic Program Product Of Service Solution (SPSS) Windows version 17.These results indicate that the effect of animated films Upin and Ipin on the application of social value students at SDN 006 Sekolubuk Tigo Lirik, that the value of R = 0.733 and the coefficient of determination (Rsquare) amounted to 0.537 with a significance level of 0.001 is smaller than Î± = 0.05. The figure shows the understanding that the contribution of variables influence the animated film Upin and Ipin on the application of social value students obtained was 53.7% with a strong influence category.Keyword: Animation Film, Sosial Value of Application